Densities, viscosities, speeds of sound and refractive indices for binary mixtures of N-Vinyl-2-pyrrolidinone with n-Alcohols (C4-C7) at 293.15 to 313.15 K. (4th May 2022) - Sharma, Chandani; Bakshi, Ankush; Kumar, Ashwani; Bamezai, Rajinder K.
ABSTRACT: Density ( ρ ), speed of sound ( u ), viscosity ( n ) and refractive index ( nD ) of binary liquid mixtures comprising of N-vinyl-2-pyrrolidinone + 1-butanol, + 1-pentanol, + 1- hexanol and + 1-heptanol are accurately measured over the entire range of mole fractions at different temperatures (293.15 to 313.15) K and atmospheric pressure. Utilising the basic experimental data, various excess thermodynamic functions such as excess molar volume ( V E ), deviation in viscosity ( Δη ), deviation in the speed of sound ( Δu ), deviation in isentropic compressibility ( ΔKs, ), deviation in refractive index ( ΔnD ) and excess Gibbs-free energy of activation of viscous flow ( ΔG * E ) were calculated. To estimate the binary coefficients and standard deviation between the calculated and experimental values, the excess values were fitted to the Redlich−Kister polynomial equation. The analysis of these functions depicts the existence of specific and non-specific interactions.